The integration of omics: A promising approach to personalized tuberculosis treatment - Priyanka Guha; Siddhartha Dutta; Krishna Murti; Jay Karan Charan; Krishna Pandey; V. Ravichandiran; Sameer Dhingra (Medicine in Omics)
Tuberculosis (TB) continues to be a global health problem due to its high morbidity and death rates. Standardized regimens have been used in traditional TB treatment methods, frequently leading to less-than-ideal results and the establishment of drug-resistant strains. The development of personalized medicine provides a potentially effective remedy to individual patients' by adjusting therapeutic approaches to particular genotypic and phenotypic traits. Detecting TB strains, drug resistance indicators, and host genetic variants that affect treatment results is made possible by genomic and molecular diagnostic approaches. These developments offer helpful information for predicting therapy outcomes and choosing the best treatment plan for each individual.Integrating phenotypic data, such as clinical characteristics, immunological state, and comorbidities, improves diagnostic and treatment decision-making accuracy. The use of targeted drug therapies, such as innovative anti-TB medicines and repurposed medications, which have the potential to overcome drug resistance and boost treatment effectiveness, can be guided by personalized therapy. Personalized interventions based on genetic and phenotypic factors can improve patient outcomes by identifying those at risk of treatment failure or disease progression. This article discusses the importance of personalized therapy for TB patients. It specifically highlights the benefits of using “omics” data to enhance therapeutic results and decrease the risk of drug resistance.